ANALISIS EFEKTIVITAS VIDEO MOTION GRAPHIC SEBAGAI MEDIA PROMOSI UMKM DI KABUPATEN PEMALANG - Muhamad Topan Dinar; Imam Tahyudin (LPPM Universitas Abdurrab, 2026)
Digital transformation has become a primary determinant in business communication effectiveness, yet MSMEs in the DM Kuliner area of Pemalang Regency still rely on static, conventional promotional formats. This study aims to examine the effectiveness of using motion graphics videos as a multimedia tool to improve usability perceptions and information acceptance among MSME operators. Using a One-Group Pretest-Posttest design, data were collected from 21 respondents using the System Usability Scale (SUS) instrument, which had been rigorously tested for validity and reliability. Data analysis was comprehensively conducted through descriptive statistics, the Shapiro-Wilk normality test, and hypothesis testing using the Paired Sample T-Test via SPSS. The results showed a significant increase in the overall mean SUS score from 62.26 in the pre-test phase to 69.64 in the post-test phase. Based on Acceptability Ranges mapping, this promotional medium successfully transitioned from the